Systematic Literature Review: The Role of Human Resource Development in Employee Performance - Briyantoro, Mekky (International Journal of Business, Law, and Education, 2025)
Human resource development plays a crucial role in ensuring the long-term success and sustainability of organizations or businesses. This research is conducted to explore how human resource development contributes to enhancing employee performance. The study employs a systematic literature review as its research methodology. For data analysis, bibliometric techniques are utilized, supported by VosViewer software version 1.6.1.9. Findings from the reviewed literature suggest that effective human resource development initiatives positively influence employee performance. Therefore, it can be concluded that investing in human resource development is essential for organizations seeking to improve their employees' competencies, abilities, and overall productivity. The study also highlights the significance of aligning developmental programs with both individual career goals and organizational strategies